Circular Bioeconomy and the Forest-Wood Sector: Bridging the Gap between Policies and Disadvantaged Forest Areas - Massimiliano Borrello; Elisa Altomonte; Luigi Cembalo; Valentina D’Amico; Alessia Lombardi (Applied Sciences, 2023)
The adoption of circular bioeconomy (CBE) strategies in forest-wood supply chains is a possible avenue for the future of this sector. However, the uptake of CBE models may face several barriers in the coming years, particularly in disadvantaged forest areas lacking appropriate resources and a suitable business environment to start radical innovation pathways. Based on interviews with 29 representatives (business actors and other key informants) of the forest-food sector of the Salerno province (Italy), the current study investigated the main strengths, weaknesses, opportunities, and threats (SWOT) involved in the transition of disadvantaged forest areas into a circular bioeconomy. Respondents also contributed to identifying the most suitable strategies in order to foster the CBE transition in the territory at hand. The paper offers an outlook for the potentialities of CBE in disadvantaged forest areas for policy actors, willing to bridge the gap between CBE agendas and territorial development challenges. The role of policy actors is particularly crucial, in order to patronize investments, stimulate improved know-how and cooperation, and fix policy inconsistencies related to biomass valorization.